FREQUENCY OF VENTRICULAR SEPTAL RUPTURE AS A COMPLICATION OF ACUTE ST-ELEVATION MYOCARDIAL INFARCTION IN PATIENTS PRESENTING TO A TERTIARY CARE HOSPITAL - Shahsawar,; Mati ur Rehman,; Muhammad Hammad Sharif,; Zeeshan Afzal, (Journal of Ayub Medical College Abbottabad, 2022)
Background: Nearly one-third of the world's population dies from cardiovascular disorders, the majority of which are caused by stroke and coronary artery problems and 80 percent of these fatalities occur in impoverished countries. This study was conducted to determine the frequency of ventricular septal rupture in patients with acute ST-elevation myocardial infarction presenting to cardiology unit Hayatabad Medical Complex Peshawar. Methods: This was descriptive cross sectional research study at the Department of Cardiology, MTI-Hayatabad Medical Complex, Peshawar, from January to July 2020. Detailed history was obtained including duration of symptoms, co-morbidities present and occupation. A thorough clinical examination was done for signs of heart failure and ventricular septal rupture. Patients' demographics, clinical and laboratory parameters were recorded on a pro forma. All the data was analyzed statistically by using SPSS version 24.0. Results: A total of 179 patients were included in our study. Ventricular Septal Rupture (VSR), was recorded in 7 (3.9%) patients having Acute ST elevation of MI. In our study age, obesity, reperfusion therapy, location of MI and history of previous shock were observed to be non-significantly (pË‚0.05) associated with high incidence of Ventricular Septal Rupture in patients having Acute ST elevation of MI. Conclusion: According to our findings, individuals with PI-VSR have a significant risk of acute-phase death. Furthermore, a significant incidence of acute-phase fatalities has been related to female gender and severe cardiac failure upon admission.